Porcine Y-chromosome variation is consistent with the occurrence of paternal gene flow from non-Asian to Asian populations. (January 2018) - Guirao-Rico, Sara; Ramirez, Oscar; Ojeda, Ana; Amills, Marcel; Ramos-Onsins, Sebastian
Abstract Pigs (Sus scrofa ) originated in Southeast Asia and expanded to Europe and North Africa approximately 1 MYA. Analyses of porcine Y-chromosome variation have shown the existence of two main haplogroups that are highly divergent, a result that is consistent with previous mitochondrial and autosomal data showing that the Asian and non-Asian pig populations remained geographically isolated until recently. Paradoxically, one of these Y-chromosome haplogroups is extensively shared by pigs and wild boars from Asia and Europe, an observation that is difficult to reconcile with a scenario of prolonged geographic isolation. To shed light on this issue, we genotyped 33 Y-linked SNPs and one indel in a worldwide sample of pigs and wild boars and sequenced a total of 9903 nucleotide sites from seven loci distributed along the Y-chromosome. Notably, the nucleotide diversity per site at the Y-linked loci (0.0015 in Asian pigs) displayed the same order of magnitude as that described for autosomal loci (~0.0023), a finding compatible with a process of sustained and intense isolation. We performed an approximate Bayesian computation analysis focused on the paternal diversity of wild boars and local pig breeds in which we compared three demographic models: two isolation models (I models) differing in the time of isolation and a model of isolation with recent unidirectional migration (IM model). Our results suggest that the most likely explanation for the extensive sharing of one Y-chromosome haplogroup between non-Asian and Asian populations is a recent and unidirectional (non-Asian > Asian) paternal migration event.